Screening bisphenols in complex samples via a planar Arxula adeninivorans bioluminescence bioassay - Jaber, Max; Jähne, Martin; Oberle, Michaela; Morlock, Gertrud E.; Justus Liebig University Giessen (My University, 2023)
The Arxula yeast bisphenol screen (A-YBS) utilizes the bioluminescent Arxula adeninivorans yeast–based reporter cells for tailored analysis of bisphenols, one of the major endocrine-disrupting compound groups. For the first time, this bioreporter has been applied on the high-performance thin-layer chromatography (HPTLC) adsorbent surface to develop a respective planar bioluminescence bioassay (pA-YBS). The goal was to combine the advantages of HPTLC with a more selective bioassay detection for bisphenols. The performance of this pA-YBS bioluminescence bioassay was demonstrated by calculating the half-maximal effective concentration (EC50) of bisphenols compared to references. The EC50 ranged from 267 pg/band for bisphenol Z and 322 pg/band for bisphenol A (BPA) to > 1 ng/band for other bisphenols (BPC, BPE, BPF, and BPS) and references (17β-estradiol and 17α-ethinylestradiol). The EC50 value of BPA was three times more sensitive in signal detection than that of 17β-estradiol. The visual or videodensitometric limit of detection of BPA was about 200 pg/zone. The higher signal intensity and sensitivity for BPA confirmed the tailored bioassay selectivity compared to the existing estrogen screen bioassay. It worked on different types of HPTLC silica gel plates. This HPTLC–UV/Vis/FLD–pA-YBS bioluminescence bioassay method was used to analyze complex mixtures such as six tin can migrates, five thermal papers, and eleven botanicals. The detected estrogenic compound zones in the tin can migrates were successfully verified via the duplex planar yeast antagonist estrogen screen (pYAES) bioassay. The two bisphenols A and S were identified in one out of five thermal papers and confirmed with high-resolution mass spectrometry. No bisphenols were detected in the botanicals investigated via the pA-YBS bioluminescence bioassay. However, the botanicals proved to contain phytoestrogens as detected via the pYAES bioassay, which confirmed the tailored bioassay selectivity. This HPTLC–UV/Vis/FLD–pA-YBS bioluminescence bioassay is suited for cost-efficient analysis of BPA in complex samples, with no need for sterile conditions due to the fast workflow.
Keywords: ddc:630